Study of the strength of flocculated structures of polydispersed coal suspensions - Shkop, Andrii; Tseitlin, Musii; Shestopalov, O.; Raiko, Valentina (Технологічний центр, 2017)
The influence of concentration, dispersed composition and degree of thickening of the flocculated slime on the strength of floccules was studied. It was revealed that for the formation of durable aggregates of polydispersed coal slime it is recommended to apply the combination of the non-ionogenic and anionogenic flocculant in the ratio of 20:80 % respectively. It was established that the residual sedimentation rate of floccules after mechanical influence at the constant consumption of the flocculant has the greatest value at the concentration of solid phase in slime of 10–30 g/dm3. With an increase in the content of the portion of solid phase with coarseness of more than 40 µm, the strength of floccules increases to the larger degree than the influence of the initial concentration. This makes it possible to recommend the correction of the slime composition not only by the concentration, but also by the content of medium grade of more than 15–20 %. It was shown that with an increase in the degree of thickening of more than 140–150 g/l the resistance of aggregates to mechanical influence substantially decreases due to an increase in pseudo-plastic properties of flocculated slime.

Досліджено вплив концентрації, дисперсного складу і ступеня згущення на міцність флокуляційних структур. Виявлено, що для утворення міцних агрегатів полідисперсного вугільного шламу рекомендується застосування поєднання неіоногенного і аніоногенного флокулянта, замість тільки аніоногенного. Встановлено, що міцність флокул після механічного впливу має найбільше значення при концентрації твердої фази в шламі 10–30 г/дм3 і часткою середньої фракції більше 15–20 %. Показано, що зі зростанням ступеня згущення шламу понад 140–150 г/л істотно зменшується міцність агрегатів до механічних впливів.
Дослідження міцності флокуляційних структур полідисперсних вугільних суспензій
Keywords: flocculation; polydispersed slimes; aggregate formation; strength of floccules; residual sedimentation rate; degree of slime thickening; флокуляція; полідисперсні шлами; агрегатоутворення; міцність флокул; залишкова швидкість осідання; ступінь згущення шламу